TAX DIGITALIZATION AND TAX COMPLIANCE: A SYSTEMATIC LITERATURE REVIEW - Truly Wulandari; Noviyanti Angreani; Mappa Panglima Banding; Olivia Pamilangan Andilolo; Iqrima Mas Mappangile (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2026)
This study aims to analyze the effect of tax digitalization on tax compliance and to identify research patterns and trends related to tax digitalization during the 2019–2025 period. The research method employed is a Systematic Literature Review (SLR) consisting of planning, conducting, and reporting stages. Relevant articles were systematically identified through the SINTA database based on predetermined inclusion and exclusion criteria, resulting in 21 articles selected for analysis. The findings indicate that tax digitalization contributes to improving tax compliance through enhanced ease of use, perceived usefulness, administrative efficiency, transparency, and taxpayer trust in the tax system. However, the effectiveness of digitalization is influenced by contextual factors such as digital literacy, infrastructure quality, cultural characteristics, trust in tax authorities, and regulatory readiness. Furthermore, the review reveals a shift in research trends from evaluating electronic tax system implementation toward examining taxpayer behavior, digital inclusion, the application of big data and artificial intelligence, and digital tax governance. The study concludes that tax digitalization has significant potential to improve tax compliance; however, its success depends on the development of an inclusive and adaptive ecosystem supported by adequate digital literacy, robust infrastructure, and responsive policies that accommodate technological advancements. Keywords: Tax Digitalization; Tax Compliance; E-Filing; Digital Literacy; Systematic Literature Review